2018
DOI: 10.1007/s10535-017-0754-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of reference genes for real-time quantitative PCR normalization in Ilex paraguariensis leaves during drought

Abstract: Reverse transcription of RNA followed by real-time quantitative PCR (qPCR) is to date the most reliable method for gene expression studies. However, to control the errors introduced along the numerous experimental procedures, it requires a normalization using internal reference genes with stable expression. To address this issue, nine candidate reference genes were investigated in Ilex paraguariensis leaves subjected to water stress. To facilitate the selection, we analysed the real-time qPCR data with three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…In contrast, UBQ1 and AGD11 were unstably expressed genes in L. chinense (Table 5). As a member of the UBQ family, UBQ1 did not have good expression stability in our study, and it also showed an unstable expression pattern in lettuce (Lactuca sativa) [8] and in leaves of Ilex paraguariensis under drought treatment [46]. However, UBQ1 had better expression stability in the parasitic life cycle of Striga hermonthica [10].…”
Section: Discussioncontrasting
confidence: 59%
“…In contrast, UBQ1 and AGD11 were unstably expressed genes in L. chinense (Table 5). As a member of the UBQ family, UBQ1 did not have good expression stability in our study, and it also showed an unstable expression pattern in lettuce (Lactuca sativa) [8] and in leaves of Ilex paraguariensis under drought treatment [46]. However, UBQ1 had better expression stability in the parasitic life cycle of Striga hermonthica [10].…”
Section: Discussioncontrasting
confidence: 59%
“…The reliability of the data generated in such studies is critically dependent on the identification of suitable reference genes. Such internal controls have been identified and validated for a variety of plant species (Paolacci et al 2009, Manoli et al 2012, Saha et al 2014, Acevedo et al 2018. However, to our knowledge, no systematic evaluation of appropriate reference genes in cultivated oat has yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…EF1 is stably expressed in not only P. edulis, but also other plants. For example, EF1 was used as an internal control gene in Ilex paraguariensis leaves and potato (Solanum tuberosum L.) under abiotic stress [43,44]. To our knowledge, the expression level of reference genes may change with changes in species, experimental conditions, and tissue types.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although EF1 was suitable for data normalization in P. edulis, potato under abiotic stress, drought-treated leaves of I. paraguariensis, and Betula luminifera, this gene was unsuitable for data normalization in Camellia sinensis under metal stress and in leaves of Camellia sinensis [38,[43][44][45][46]. Overall, Ts and EF1 have the highest expression stability, but if we classify all samples into different subsets, there may be other genes in each subset with higher expression stability than Ts and EF1.…”
Section: Discussionmentioning
confidence: 99%